Strategic implementation of ED&I: unveiling the multifaceted impact on innovation, governance, and ethical conduct in engineering organizations - Atescan-Yuksek, Yagmur; Patsavellas, John; Salonitis, Konstantinos (Frontiers in Industrial Engineering, 2024)
In contemporary organizational landscapes, Equity, Diversity, and Inclusion (ED&I) stand as pivotal pillars for fostering innovation, resilience, and sustainable growth. This article explores the critical importance of ED&I within engineering organizations, focusing on the strategies for understanding ED&I dynamics, implementing inclusive environments, and extending ED&I principles through the industrial value chain. It investigates the complexities of individual identities, the significance of intersectionality, and the strategic advantage of diversity for organizational performance. By exploring comprehensive governance of ED&I initiatives, the role of leadership in fostering diversity, and the impact of ED&I on organizational sustainability and innovation, this study provides a holistic view of the challenges and opportunities in creating inclusive workplaces.